A Character Strengthening Model to Address the Ethical Crisis, Value Disorientation, Digital Disinformation Based on Multiculturalism and Digital Literacy Toward Superior Human Resources 2045 - Sipayung, Tumini; Sondang, Sondang; Iranda Marcella; Ronauli Manurung (Sean Institute, 2025)
The ethical crisis, value disorientation, and the rapid spread of digital disinformation present serious challenges to the development of human resources in the digital era. These phenomena not only weaken moral foundations but also threaten social cohesion in increasingly multicultural societies. This study proposes a character strengthening model based on multiculturalism and digital literacy as a strategic framework for preparing superior human resources toward Indonesia 2045. The model integrates core character values such as integrity, responsibility, critical thinking, empathy, and respect for diversity with multicultural awareness and digital literacy competencies. Through this integrative approach, individuals are equipped to navigate ethical dilemmas, respond critically to digital information, and engage responsibly in diverse social and digital environments. The implementation of the model emphasizes collaborative involvement among educational institutions, families, communities, and government, supported by contextual learning strategies and ethical digital practices. This model is expected to strengthen moral resilience, promote social harmony, and enhance digital intelligence, thereby contributing to the formation of ethically grounded, culturally inclusive, and digitally competent human resources capable of supporting sustainable national development toward Indonesia 2045.